The Effects of Food Insecurity on College Students - Kelly, Maxfield Adrien (URJ-UCCS: Undergraduate Research Journal at UCCS, 2022)
Food insecurity (FI) relating to college students has been a subject that has bound arguments over cause and effectto one particular understanding. Discourse over the legislation has become fundamental in creating steps that arefocused on solving the effects of FI on college students relating to a micro-level. Food insecurity must first be solvedon a small scale to be effective on a larger scale. The importance of finding new ways to stop the spread of FI lies inunderstanding how hunger can affect students. Realistically, for students to function with high cognitive ability, thebody must obtain nutrients only available through eating food, with healthy food being the most useful for hungryorgans like the brain. The cost of nutrition is especially important for college students who must balance budgets byjuggling school, rent, food, and lifestyle choices among other things. This paper explores the importance of students,and general audience members alike, understanding the steps associated with mitigating the effects of food insecurityby creating activism that involves the members of local communities and thus effectively creating positive change thatanyone can become a part of.